Twentieth-century American art - Doss, Erika (Oxford University Press, 2002)
Jackson Pollock, Georgia O'Keeffe, Andy Warhol, Julian Schnabel, and Laurie Anderson are just some of the major American artists of the twentieth century. From the 1893 Chicago World's Fair to the 2000 Whitney Biennial, a rapid succession of art movements and different styles reflected the extreme changes in American culture and society, as well as America's position within the international art world...